Jogos e a aprendizagem híbrida : desafios e possibilidades didáticas colaborativas no ensino de Genética - Costa, Luciele Matos do Carmo (2021)
In view of the weaknesses during the learning process, and here more specifically in the teaching of Biology, we seek in the active learning methods the alternative as a facilitating resource in the teaching of genetics. In this context, the present research raised the following question: What methodological perspectives would be effective for us to apply in our daily life in the classroom, aiming to facilitate the process of learning genetic concepts? The general objective of the present research was to develop strategies of Active Learning Methods (MAA) for the teaching of Biology related to Genetics, for the strengthening of the pedagogical practice. The research has a qualitative approach and proposed to discuss active learning methods and those located in the hybrid teaching zone. We employ some elements of the Delphi Method with specialists in the field of Genetics and teaching in Basic Education. The experts collaborated with the research by evaluating the material produced and brought suggestions for its improvement. After the analysis and adjustments, we suggest a script with collaborative teaching possibilities and the development of a game, entitled “HEBIO”, in order to facilitate the learning process in the teaching of Genetics. From the perspective of the experts, the relevance of the game in the teaching of genetics was found, through the results obtained. The research allowed us to consider that the active learning methods, especially the games, can be pointed out as facilitating learning tools through the mediation of an interactive teacher, which allows the development of inclusive and collaborative principles, with a focus on the student's role in the process of your own learning.